Homeostatic regulation of hepatocyte nuclear transcription factor 1 expression in cultured hepatoma cells. - Pietrangelo, A (1994)
Serum colloid osmotic pressure is believed to control the hepatic output of plasma proteins, including albumin. The present study was aimed at identifying the molecular basis for feedback control of albumin gene expression in highly differentiated hepatoma cells. The steady-state level of albumin mRNA and the activity of a 282-bp albumin promoter-chloramphenicol acetyltransferase reporter gene in cells incubated in the presence of increasing amounts of serum albumin or dextran were significantly and selectively decreased. When nuclear extracts from cells exposed to 5% (wt/vol) serum albumin were tested in a gel-retardation assay with six oligonucleotide probes containing DNA elements of the albumin promoter, only the element B-retarded band, which contains the nucleotide recognition sequence for hepatocyte nuclear transcription factor 1 alpha (HNF-1 alpha), was consistently decreased as compared to nuclear extract from cells not exposed to serum albumin. Moreover, the activity of a reporter gene with a basal TATA-promoter driven by multiple HNF-1 alpha recognition elements was selectively inhibited in cells incubated in the presence of 5% serum albumin. A reduction of HNF-1 alpha mRNA appears to be responsible for this response to a change in the level of macromolecules in the incubation medium. These results indicate that activity of a dominant liver transcription factor, HNF-1 alpha, controlling the transcription of several liver-specific genes, is modulated by a fluctuation in the level of oncotically active macromolecules.